Sistem Pengambilan Keputusan Rekomendasi Pemberian Kredit dengan Metode Simple Additive Weighting - Putri, Weni Lestari (LPPM STIKOM Tunas Bangsa, 2023)
The decision-making system produces recommendations for parties entitled to obtain loans in accordance with predetermined provisions. There are 5 criteria that are used as a reference in providing credit loans in terms of Characteristics, Capacity, Condition, Capital and Collateral. Each criterion has a different value so a Simple Additive Weighting (SAW) method is needed to produce a decision. The way the Simple Additive Weighting (SAW) method works is by entering each weight value in each criterion. The advantage of the SAW method is that it has the ability to carry out assessments more precisely because it is based on the criteria values and preference weights that have been determined and can select the best alternative from a number of existing alternatives, apart from that because there is an improvement process after determining the weight value for each attribute. The final results of the research recommended obtaining a loan in the name of Kamedia Kemala with a value of 0.8248.